Optimalisasi Pelatihan Dan Pengembangan SDM di Dunia Pendidikan: Peran Strategis Dan Tantangan Nyata - Hery Irawan; Aris Muhamad Syukur; Osly Usman (Pusat Riset dan Inovasi Nasional, 2025)
Training and development of human resources (HR) in education has a very important role in improving the quality of education in the globalisation and digital era. This journal aims to thoroughly examine how the optimisation of training and human resource development can be done strategically, taking into account the existing challenges. Through a qualitative approach and literature review, this study identifies the importance of competency-based training planning, technology integration in HR development, and evaluation of the impact on education quality. The results of this study show that the implementation of innovative strategies such as blended learning, multi-stakeholder collaboration, and the establishment of a culture of continuous learning, can improve the effectiveness of training. This research is expected to make theoretical and practical contributions to education human resource management in Indonesia.